2005
DOI: 10.2307/3647695
|View full text |Cite
|
Sign up to set email alerts
|

Structural Choices and Representational Biases: The Post-Election Color of Representation

Abstract: Representation scholars link descriptive representation of blacks and Latinos in legislative bodies to substantive policy representation. We examine this relationship on local school boards where issue salience is high, the cost of gaining legislative access is relatively low, and nonpartisan elections produce a greater likelihood of linking policy preferences to racial cues. Theoretically, we connect substantive representation to the method of election; blacks and Latinos elected at-large face different const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 23 publications
3
79
1
Order By: Relevance
“…Once Latino Democrats are elected to office, they are uniformly more liberal than non-Latino Democrats and all Republicans regardless of the relative size of the Latino population in their district. This finding leads to a slightly different conclusion than previous findings regarding the role of majority-minority districts on policy outputs that do not account for the individual behavior of minority representatives (Meier et al 2005). Instead of a direct effect of majority-minority districts on descriptive representatives' quality of minority advocacy, state legislative majority-minority districts act indirectly by substantially increasing the likelihood of electing descriptive representatives who are themselves unique policy advocates.…”
Section: Latino Majority-minority Districts and Legislative Behaviorcontrasting
confidence: 87%
See 1 more Smart Citation
“…Once Latino Democrats are elected to office, they are uniformly more liberal than non-Latino Democrats and all Republicans regardless of the relative size of the Latino population in their district. This finding leads to a slightly different conclusion than previous findings regarding the role of majority-minority districts on policy outputs that do not account for the individual behavior of minority representatives (Meier et al 2005). Instead of a direct effect of majority-minority districts on descriptive representatives' quality of minority advocacy, state legislative majority-minority districts act indirectly by substantially increasing the likelihood of electing descriptive representatives who are themselves unique policy advocates.…”
Section: Latino Majority-minority Districts and Legislative Behaviorcontrasting
confidence: 87%
“…Previous scholarship on U.S. congressional elections has demonstrated that this is the case for African Americans and Latinos (Canon 1999;Lublin 1997b), while other evidence implies that these districts provide the same mechanisms at the state and local level (Handley, Grofman, and Arden 1998;Meier et al 2005). In political contexts like the United States, where racial and ethnic group voting is a continuing phenomenon, the likelihood of electing a minority candidate is very low in Anglo-majority districts but increases substantially, from possible to probable, after the majority-minority condition is met.…”
Section: A Model Of Majority-minority Districts Representation and mentioning
confidence: 95%
“…Studies have consistently shown that Latinos are less likely to be elected to school boards that use at-large electoral systems (Fraga & Frost, 2010;Fraga, Meier, & England, 1986;Meier & Gonzalez Jeunke, 2005;Meier & Stewart, 1991; for one California study that found no effect, see Fraga & Elis, 2009). Meier, Gonzalez Juenke, Wrinkle, and Polinard (2005) also find that the electoral structure under which representatives get elected to school boards affect their policy preferences once in office, particularly their support for hiring Black and Latino administrators.…”
Section: Voting and School Board Representationmentioning
confidence: 95%
“…Several explanations, perhaps working in concert, may account for why BEST performs well in this context. First, Meier et al (2005) argue that nonpartisanship increases the influence of black board members from ward-based single-member districts by encouraging fluid coalition patterns. Second, as Tucker and Zeigler (1978) point out, educators believe they provide a specialized service to a narrow clientele-students-rather than the public at large.…”
Section: Evidence Informing the Debatementioning
confidence: 99%
“…Furthermore, smaller legislative bodies may advantage minority lawmakers by conferring greater power upon individuals. As Meier et al (2005) explain, the likelihood of one minority lawmaker casting a decisive vote on a five-person board is greater than the likelihood of a small group of minorities (e.g., 20) doing so within a 435-person legislature. Further, smaller legislative bodies typically have fewer procedural rules constraining individual influence because the need for institutional productivity is less pressing.…”
Section: Evidence Informing the Debatementioning
confidence: 99%